Improving Soybean Seed Sucrose Content using TILLING by Sequencing Analyses of The Soybean Sucrose Synthase Gene Family - Dounya Knizia; Erdem Anil; Yasser Salhi; Haiying Shi; Abdelhalim El Baze; My Abdelmajid Kassem; Naoufal Lakhssassi; Henry T. Nguyen; Khalid Meksem (Frontiers in Plant Science)
Soybean seed quality is influenced by its soluble sugar composition, with high sucrose content being desirable for nutritional and industrial applications. In contrast, excessive raffinose and stachyose levels are considered undesirable due to their adverse effects on gastrointestinal function in humans and monogastric animals. Therefore, developing soybean mutant lines with elevated sucrose content and optimal raffinose and stachyose content is desirable. In this study, we characterized twelve sucrose synthase genes through a comprehensive phylogenetic tree analysis, synteny analysis, gene structure evaluation, and variations in conserved domains. Additionally, we conducted a TILLING by Sequencing approach to identify EMS mutations in the characterized Sucrose synthase genes. Numerous mutations have been identified in soybean sucrose synthases that resulted in high sucrose content, including the sucrose synthases mutants SL446 (R582W) and F1115 (G249E) on Glyma.02G240400 with a sucrose content of 9.5% and 9.1%, respectively. The obtained soybean mutants with enhanced sugar content can be useful in breeding programs to improve soybean nutritional quality without potential developmental trade-offs.